The Vietnamese Wetlands Classiíication System - Nhuan, Mai Trong; Thu Ha, Nguyen Thi; Quy, Tran Dang; Ngoc, Nguyen Thi; Thuy Linh, Do Thi; Minh Ngoc, Nguyen Thi; Hong Hue, Nguyen Thi; Ngoc, Pham Bao (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 2, 2008)
Abstract